2012
DOI: 10.1016/j.jprot.2012.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific phosphorylation of protein phosphatase 1 regulatory subunit 12A stimulated or suppressed by insulin

Abstract: Protein phosphatase 1 (PP1) is one of the major phosphatases responsible for protein dephosphorylation in eukaryotes. So far, only few specific phosphorylation sites of PP1 regulatory subunit 12A (PPP1R12A) have been shown to regulate the PP1 activity. The effect of insulin on PPP1R12A phosphorylation is largely unknown. Utilizing a mass spectrometry based phosphorylation identification and quantification approach, we identified 21 PPP1R12A phosphorylation sites (7 novel sites, including Ser20, Thr22, Thr453, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Inhibitor experiments indicated that the interaction of PPP1R12A and PP1cδ with IRS1 is diminished upon inhibition of Akt and mTOR/Raptor [20]. Moreover, we have demonstrated that insulin stimulates or suppresses multiple phosphorylation sites of PPP1R12A [21]. These results provided the first evidence that PPP1R12A may regulate skeletal muscle insulin action through tuning PP1cδ activity and specificity.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Inhibitor experiments indicated that the interaction of PPP1R12A and PP1cδ with IRS1 is diminished upon inhibition of Akt and mTOR/Raptor [20]. Moreover, we have demonstrated that insulin stimulates or suppresses multiple phosphorylation sites of PPP1R12A [21]. These results provided the first evidence that PPP1R12A may regulate skeletal muscle insulin action through tuning PP1cδ activity and specificity.…”
Section: Introductionmentioning
confidence: 84%
“…However, a mechanism for serine/threonine phosphatase action in insulin signal transduction is largely unknown. Recent evidences from our group suggest that PPP1R12A, a regulatory subunit of protein phosphatase 1, is involved in insulin signaling [1921]. Moreover, the majority of research on the abnormalities of phosphorylation in skeletal muscle insulin action focuses a few known phosphorylation targets.…”
Section: Discussionmentioning
confidence: 99%
“…PP1R12A is a member of the major group of phosphatases in eukaryotes. Therefore, its phosphorylation seems to play a key role in the insulin signal transduction, because this hormone stimulates PP1R12A phosphorylation at several sites, including Ser 507 (80). To determine over-represented sequence motifs from the whole as well as regulated phosphoproteome dataset, we performed the motif-X algorithm (41) using the Homo sapiens database as background.…”
Section: Phosphorylation and N-linked Sialylation As Important Ptms Fmentioning
confidence: 99%
“…This is one of several sites in MYPT1 reported by Cell Signaling Technology using LC-MS/MS platform to be phosphorylated in a number of human cancers [48]. Insulin has also been shown to result in MYPT1 phosphorylation at Ser668 [49], although neither the function of this phosphorylation nor the responsible kinase have been identified. Protein kinase G (PKG1α) known to selectively phosphorylate MYPT1 isoforms that include a C-terminal leucine zipper has also been shown to phosphorylate MYPT1 on Ser668 in vitro [50].…”
Section: Discussionmentioning
confidence: 96%